Antioxidant and immunomodulatory activities of ethanol extracts from Syzygium cumini L. Skeels and Pogostemon cablin Benth - Faradilla, Meutia; Fidrianny, Irda; Iwo, Maria I. (Narra J, 2024)
Syzygium cumini and Pogostemon cablin are mostly cultivated in tropical climates for culinary and perfumery purposes, yet their potential medicinal properties remain underreported. The aim of this study was to examine the antioxidant and immunomodulatory activities of ethanol extracts from S. cumini (EESC) and P. cablin (EEPC). Reflux extraction was carried out using 96% ethanol on the collected plant specimens to produce EESC and EEPC. Secondary metabolites of each extract were identified using gas chromatography-mass spectrometry (GC-MS). The extracts were measured for total phenol and flavonoid levels and 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity. The immunomodulatory activity test was carried out in vivo by assessing several parameters, including the phagocytic index via the carbon clearance method, organ indices, antibody titers, and delayed-type hypersensitivity (DTH) response, using sheep red blood cells (SRBC) as antigens. The extracts were also examined for their anti-inflammatory activity in acute and chronic inflammation models. In the DPPH antioxidant test, EESC and EEPC had IC50 values of 12.33 µg/mL and 182.17 µg/mL, respectively. Both extracts showed immunosuppressant activity, marked by a phagocytic index of <1. EESC yielded lower organ indices for the liver (p=0.025 at 200 mg/kg BW), spleen (p=0.028 at 100 mg/kg BW), and thymus (p=0.032 at 200 mg/kg BW) compared to the control group. For EEPC, lower organ indices were observed in the liver at 100 mg/kg BW (p=0.005) and 200 mg/kg BW (p=0.031). In the primary antibody titer and DTH tests, both EESC and EEPC showed immunosuppressant activity at 200 and 400 mg/kg BW (p<0.05). The extracts suppressed both the innate and adaptive immune systems. Both EEPC (p=0.004) and EESC at 100 mg/kg BW (p=0.03) significantly reduced serum TNF-α levels. In conclusion, EESC and EEPC have the potential as immunosuppressive and anti-inflammatory agents.